DEVELOPING GROUP LEADERSHIP AND COMMUNICATION SKILLS FOR MONITORING EVM IN PROJECT MANAGEMENT (Journal of Mechanical Engineering, 2015)
Earned Value Management (EVM) is used to track the progress and status of a project with forecasting future performance. Leaders use the Evaluation, Verification and Monitoring with Earned Value Management (EVM) technique to evaluate their project progress and performance as an early warning tool. Monitoring EVM involves determining whether the project is on, ahead of, or behind schedule and on, under or over budget. Usually an organization has many people with many multi-dimensional strategic ideas. All of these people are focused on ultimate end points, they work on the same target, they play on the same field, and they gain their knowledge about the same markets and share their ideas with personal confident. They rely on EVM which integrates cost, schedule and scope to capture project progress assessment and project completion update.